Transformações geométricas: ações e aplicações nos anos finais do ensino fundamental - Casarin, Jones Ueder (2023)
The present study deals with the mathematical content of geometric transformations, taking as a source of inspiration the fact that it is little explored, often due to gaps in the teacher's knowledge in relation to this topic. Therefore, the main objective is to investigate the importance of the content of geometric transformations within the development of students' geometric thinking, in order to identify practices that best meet the theoretical foundations related to the subject. In addition to bibliographical research, activities will also be applied and elaborated with digital technologies and works of art, to work with homothety and isometries, such as rotation, translation and reflection, in order to contemplate the skills required by the current National Common Curricular Base ( BNCC). The participants of the applications are 37 students from the 6th and 7th years of elementary school in a municipal public school in the interior of Rio Grande do Sul. It is concluded that from the application of the activities, objects proposed by the curricular guidelines were reached, in addition to obtaining extraordinary interaction of the students in the activities with the use of computational tools. It is hoped that this work can support fellow mathematics teachers and inspire them to continue creating activities and accept the theme as important for the development of student learning.